A stand‐alone tree demography and landscape structure module for Earth system models. Issue 19 (8th October 2013) - Haverd, Vanessa; Smith, Benjamin; Cook, Garry D.; Briggs, Peter R.; Nieradzik, Lars; Roxburgh, Stephen H.; Liedloff, Adam; Meyer, Carl P.; Canadell, Josep G.
Abstract [1] We propose and demonstrate a new approach for the simulation of woody ecosystem stand dynamics, demography, and disturbance‐mediated heterogeneity suitable for continental to global applications and designed for coupling to the terrestrial ecosystem component of any earth system model. The approach is encoded in a model called Populations‐Order‐Physiology (POP). We demonstrate the behavior and performance of POP coupled to the Community Atmosphere Biosphere Land Exchange model (CABLE) applied along the Northern Australian Tropical Transect, featuring gradients in rainfall and fire disturbance. The model is able to simultaneously reproduce observation‐based estimates of key functional and structural variables along the transect, namely gross primary production, tree foliage projective cover, basal area, and maximum tree height. Prospects for the use of POP to address current vegetation dynamic deficiencies in earth system modeling are discussed.